The Critical Path and Other Writings on Critical Theory, 1963-1975 - Frye, Northrop (Book collections on Project MUSE., 2009)
This volume, which collects Northrop Frye's writings on the theory of literary criticism from the middle period of his career, includes one of Frye's own favourites, The Critical Path (1971). A highly important marker of Frye's career, The Critical Path openly addresses topics that he had previously been reluctant to discuss as fully, including the importance of literature to society, the responsibilities of critics, and the deeper rationales for studying literature.Filled with insightful texts that indicate his transition from literary critic to a theorist of language, myth, and human culture, this edition helps to illuminate many of the ideas and arguments that would appear later in The Great Code and Words with Power. Accompanied by the rigorous scholarship for which the series is renowned, this is another valuable contribution to literary criticism and theory.